44. Breaking Down the LMS Walls - Hotrum, Michael (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2005)
The traditional packaging of electronic learning — the learning management system (LMS) — is progressively being regarded as a hindrance to effective online learning. Its design, functionality, complexity, price, and value are being questioned. A new generation of Web-based tools and approaches is evolving that are better suited to meet the need for dynamic online learning content, interaction, collaboration, and networking. Whereas traditional LMS approaches traditionally tend to relegate students to the role of passive recipients of information, these new tools and collaborative approaches allow learners to take proactive control of their own learning. This paper will discuss how the LMS has affected the design and delivery of e-learning, and the emerging technologies that are better suited to current learning and performance needs. “All in all it was just a brick in the wall. All in all it was all just bricks in the wall.” (Pink Floyd, November 30, 1979)The Internet is independent of device (hardware or platform), distance, and time, and is well-suited for open, flexible, and distributed learning. Yet traditional online, distributed learning methods are anything but flexible, open, or dynamic. What went wrong? Parkin (2004a, b) believes that we failed to appreciate that the Internet is a vehicle for connecting people with each other. We implemented LMS methods that imposed bureaucratic control, diminished learner empowerment, and delivered static information. “In a world hurtling toward distributed internetworking, e-learning was still based on a library-like central-repository concept.” Parkin suggests it is time to explore the true promise of e-learning, and to rework our ideas about how learning should be designed, delivered, and received. It is time to stop letting the LMS vendors tell us how to design learning. It is time to stop the tail from wagging the dog.